Nursing Activities Score is increased in COVID-19 patients - Lucchini, Alberto; Giani, Marco; Elli, Stefano; Villa, Silvia; Rona, Roberto; Foti, Giuseppe (Intensive & critical care nursing, 2020)
[...]four other COVID-ICUs were created in the hospital. Since 2005, in our ICU we have been recording the Nursing Activities Score (NAS) of all admitted patients daily, to measure the nursing workload. Use of protective devices increases body temperature and is tolerable only for a few hours. [...]we re-organised shifts to allow resting for one nurse at a time outside the “contaminated area”, in order to guarantee a rotation every 2–3 hours for operators dedicated to isolated patients. Unfortunately, the need to provide an enormous amount of new ICU beds makes it impossible to guarantee this nurse-to-patient ratio. [...]we suggest to colleagues worldwide to make an effort to increase the ICU nursing staff, starting to train registered nurses from general wards to perform basic ICU procedures and to dedicate intensive care nurses to manage more complex procedures, in order to be prepared to face the epidemic.